Achieving gender equality, women's empowerment and strengthening development cooperation: dialogues at the Economic and Social Council (United Nations, 2010)
This publication presents the key debates that took place during the 2010 High-level Segment of the Economic and Social Council, at which ECOSOC organized its second biennial Development Cooperation Forum. The discussions also focused on the theme of the 2010 Annual Ministerial Review, "Implementing the internationally agreed goals and commitments in regard to gender equality and the empowerment of women"--Publisher's description